Dom Helder Camara, les puissants et les pauvres: pour une histoire de l'Église des pauvres dans le Nordeste brésilien; (1955 - 1985) - Marin, Richard (Églises, sociétés, 1995)
"A corrective to hagiographies, argues that Dom Helder Câmara's symbolic importance was inflated by critics' demonizing rhetoric and by statements he issued abroad while silenced in Brazil, 1970-77. First, the antiquated structure of the Archdiocese of Recife-Olinda (1964-69), and then the crisis of the priesthood (1970-85), limited the impact of his reforms. Recife was not much different from other dioceses in level of state repression or depth of reform"--Handbook of Latin American Studies, v. 58